2005
DOI: 10.1111/j.1651-2227.2005.tb01984.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing beractant and poractant treatment in neonatal respiratory distress syndrome

Abstract: Aim: To compare the effects of beractant and poractant in neonatal respiratory distress syndrome (RDS). Methods: Infants with RDS were randomized to receive beractant or poractant. The primary outcome measure was fraction of inspired oxygen (FiO2) requirement in the first 48 h after surfactant therapy. Results: 58 infants completed the study. The mean gestational ages for the poractant and beractant groups were 29.6±3.6 and 29.3±2.9 wk, with average birthweights of 1394±699 and 1408±534 g, respectively. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…11,12 Baroutis et al 21 reported a shorter mechanical ventilation course and LOS in the poractant-treated group, whereas Speer et al 22 and Fujii et al 18 found a lower MAP requirement in the poractant-treated group. Malloy et al 9 found that premature infants treated with poractant had a lower FiO 2 requirement post-surfactant administration. Meanwhile, our study showed no significant difference in the mode of ventilation, FiO 2 requirement, duration of mechanical ventilation, oxygen supplementation, or LOS between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Baroutis et al 21 reported a shorter mechanical ventilation course and LOS in the poractant-treated group, whereas Speer et al 22 and Fujii et al 18 found a lower MAP requirement in the poractant-treated group. Malloy et al 9 found that premature infants treated with poractant had a lower FiO 2 requirement post-surfactant administration. Meanwhile, our study showed no significant difference in the mode of ventilation, FiO 2 requirement, duration of mechanical ventilation, oxygen supplementation, or LOS between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results some previous studies which compared the effectiveness of poractant and beractant failed to show any difference in mortality. [11][12][13][14][15] However, Ramanathan et al evaluated 293 infants at GAs <32 weeks with RDS and showed that an initial dose of 200 mg/kg poractant alfa resulted in a greater reduction in mortality compared to an initial dose of 100 mg/kg poractant alfa and 100 mg/kg beractant. 16 Moreover analysis of 14 173 preterm infants showed that poractant alfa reduced mortality more than beractant in preterm infants weighing 500-749 g, but this effect was not as pronounced in preterm infants weighing 1000-1249 g. 17 In our study, both surfactant preparations had similar rates of mortality even the both groups had a birth weight of <1000 g. In a recent meta-analysis administration of an initial dose of 200 mg/kg poractant alfa was shown to reduce incidence of BPD/mortality, BPD, air-leaks, pulmonary hemorrhage and need for retreatment when compared to bovine surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme preterm infants received their initial dose of BLES significantly earlier in their RDS management compared with infants born alfa has been extensively studied and has been found to result in greater improvement in oxygenation and require fewer repeated doses when compared with Beractant. 8,15,16,18 However, there are no studies specifically evaluating the length of time to wean the FiO 2 concentration to 0.21 following the administration of surfactant.…”
Section: Discussionmentioning
confidence: 99%